Water in Medieval Literature : an Ecocritical Reading. - Classen, Albrecht (Ecocritical theory and practice., 2017)
This book uncovers the tremendous importance of water for European medieval literature, focusing on a large number of writers and poets. Water proves to be highly meaningful in religious, literary, and factual narratives insofar as it emerges as a central catalyst to bring about epiphany and epistemological and spiritual illumination.